Risk factors for treatment failure in scabies. (1st April 2019) - Aussy, A.; Houivet, E.; Hébert, V.; Colas‐Cailleux, H.; Laaengh, N.; Richard, C.; Ouvry, M.; Boulard, C.; Léger, S.; Litrowski, N.; Benichou, J.; Joly, P.; et al.
Summary: Scabies is a major health problem worldwide. In developing countries, it can become infected, leading to heart and kidney disease. The prevalence of scabies is also increasing in developed countries, affecting 2‐4% of the population in Europe and USA. This is partly due to inadequate treatment. Reasons for treatment failure have been studied in hospitalised or bedbound patients, such as those with dementia in nursing homes, who are at high risk of scabies. However, treatment failure has not been studied in ambulatory individuals (i.e. who are mobile), who represent the majority of patients. The authors, based in university dermatology and biostatistics departments in Rouen, France, sought to identify predictors of treatment failure in patients who attended hospital or private dermatology clinics with a clinical diagnosis of scabies. They studied 210 patients, 98 of whom had been successfully treated and 112 who had evidence of persistent scabies 3 months after treatment. They found that a major cause of treatment failure was the use of only topical treatment (applied to the skin) with benzyl benzoate, or oral treatment (taken by mouth) with ivermectin, rather than a combination of the two. Another major cause was the use of a single dose of ivermectin rather than two consecutive doses. Other reasons for treatment failure included taking ivermectin with food rather than on an empty stomach, as recommended, inadequate treatment of relatives and close contacts, lack of written information about treatment and, perhaps, inadequate decontamination of furniture (a controversial subject). Increased frequency of application of benzyl benzoate did not seem to affect outcome, and the authors did not recommend this because of its irritancy. In conclusion, the authors felt there is a case for two consecutive doses of oral ivermectin rather than one, in addition to topical treatment. This has relevance worldwide, since single dose ivermectin is the recommended treatment in some countries.